1986
DOI: 10.1111/j.1365-2621.1986.tb11230.x
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Cooking Method on the Texture of Epimysial Tissue and Rancidity in Beef Roasts

Abstract: Twelve top round roasts from two Utility-grade cows were randomized and cooked by microwave, convection or conventional methods after epimysial tissue had been inserted into each roast. The freshly cooked and stored roasts were evaluated for rancidity using three TBA methods, and textural determinations were made on epimysial tissue. TBA numbers increased from day 0 through day 11. Shear values for epimysial tissue from S-year old animals cooked by microwave tended to be lower than those for tissues cooked by … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2010
2010
2011
2011

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 14 publications
0
4
0
Order By: Relevance
“…Increased gel strength is paralleled by a decrease in soluble protein. Welke et al (1986) observed increased weights of epimysial connective tissue after cooking, indicating hydration and hydrolysis of the collagen. No further decrease in water soluble fraction when held.…”
Section: Effect Of Heat On Proteins and Protein Structurementioning
confidence: 87%
See 2 more Smart Citations
“…Increased gel strength is paralleled by a decrease in soluble protein. Welke et al (1986) observed increased weights of epimysial connective tissue after cooking, indicating hydration and hydrolysis of the collagen. No further decrease in water soluble fraction when held.…”
Section: Effect Of Heat On Proteins and Protein Structurementioning
confidence: 87%
“…Welke et al (1986) reported roasts cooked by microwave took less time to reach endpoint temperatures than did roast cooked by convection or conventional methods. Welke et al (1986) reported roasts cooked by microwave took less time to reach endpoint temperatures than did roast cooked by convection or conventional methods.…”
Section: Dimensional Changesmentioning
confidence: 96%
See 1 more Smart Citation
“…Microwave oven cooking tends to retain higher amounts of vitamins such as retinol, thiamin, and riboflavin compared with earth-ovencooked meat. The difference in vitamin retention could be due to a higher cooking temperature of earth-oven cooking compared with microwave cooking (Welke et al, 1986;Kumar & Aalbersberg, 2006;Zhang et al 2006). In cooking process, the contractile proteins of meat (myosin and actin) will denature and the connective tissue (collagen) under goes to solubilize.…”
Section: Microwave Cookingmentioning
confidence: 99%